A Price Earnings Index for the Danish Stock Market - Ole Risager (Copenhagen Business School (CBS), Department of Economics, 2004)
Price-earnings ratios are part of the toolkit that is used for assessing the valuation of individual firms on the stock market as well as the entire market itself. This paper presents consistent P/E series for the liquid Danish shares adjusted for share buybacks. The results show that over the period from 1969 to 2003, the average (trailing) P/E equals 13.5. The P/E reaches its lowest level in 1980, which is likely to be due to a soaring oil price, high wage increases and interest rates approaching 20 percent. Notwithstanding optimistic equity pricing also in Denmark in the late 1990s, the upturn in Danish valuations was more moderate than in the US. The correction that sets in subsequently reversed essentially the gains in the Danish P/E in the 1990s.
hdl:10398/7620
Keywords: H00; 330; Price-earning; ratio